Looking glasses and neverlands : Lacan, desire, and subjectivity in children's literature - Coats, Karen, 1963- (University of Iowa Press, 2004)
This groundbreaking study introduces and explores Lacan's complex theories of subjectivity and desire through close readings of canonical children's books such as Charlotte's Web, Stellaluna, Holes, Tangerine, and The Chocolate War, providing an introduction to an increasingly influential body of difficult work while making the claim that children's textual encounters are as significant as their existential ones in constituting their subjectivities and giving shape to their desires.